The Classification of Emotions in the Character Key in the Novel Sucinya Cinta Sungai Gangga by Halimah Munawir: A Study from the Perspective of David Krech - Firdaus, Roqi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
The problem addressed in this research is how to classify the emotions of the character Key in the novel